2014
DOI: 10.5547/01956574.35.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Pricing and Tariff Differentiation: Evidence from the British Electricity Market

Abstract: Liberalisation of the British household electricity market, in which previously monopolised regional markets were exposed to large-scale entry, is used as a natural experiment on oligopolistic nonlinear pricing. Each oligopolist offered a single two-part electricity tariff, but inconsistent with current theory, the two-part tariffs were heterogeneous in ways that cannot be attributed to explanations such as asymmetric costs or variations in brand loyalty. Instead, the evidence suggests that firms deliberately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…For the UK retail electricity market, Davies et al (2014) present evidence suggesting that firms deliberately differentiated their tariff structures, resulting in market segmentation according to consumers' usage. For the US mobile telephone sector, Seim and Viard (2011) show that entry induces firms to lower prices on average and to offer larger menus with more evenly spread usage plans that give benefits to high-valuation consumers in particular.…”
Section: Introductionmentioning
confidence: 94%
“…For the UK retail electricity market, Davies et al (2014) present evidence suggesting that firms deliberately differentiated their tariff structures, resulting in market segmentation according to consumers' usage. For the US mobile telephone sector, Seim and Viard (2011) show that entry induces firms to lower prices on average and to offer larger menus with more evenly spread usage plans that give benefits to high-valuation consumers in particular.…”
Section: Introductionmentioning
confidence: 94%
“…associated with legacy networks) . In fact, Davies et al (2014) find over 63% of the variance in marginal prices and at least 82% of the variance in fixed charges can be explained by the variation within-region. Their study further suggests that asymmetric costs and other factors, including brand loyalty and market frictions, only partially influence price dispersion compared to tariff differentiation.…”
Section: Methodsmentioning
confidence: 98%
“…Nonetheless, Ofgem acknowledges that whilst some regions exhibit higher distributional charges they are, in some instances, partly offset by lower transmission charges. On the other hand, Davies et al (2014) argue that the key source of price dispersion, in a given time period, is within-region (e.g. attributed to incumbent suppliers) rather than between-regions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Stephen's research found that the ratio of fixed cost and variable cost has a systematic difference trend in different segments according to the user consumption. Thus, mutual subsidies for different segments are done through FM ratio model [12]. Klaus, from the perspective of asymmetric competition between new entrants and in-service suppliers, finds that the retailer pricing strategy may consider the information level of consumers through empirical research on German retail power market.…”
Section: Price Discrimination In Electricity Industrymentioning
confidence: 99%